Privatization and Unequal Access in India - Jamkar, Vishal; Johnstone, Christopher (International Higher Education, 2021)
The massification of Indian higher education is accompanied by a proliferation of private universities. The relaxation of several national policies has reduced the proportion of students from historically marginalized groups, while maintaining the dominance of higher caste and class students from the Hindu majority. With privatization, there is a need for stronger equity policies to avoid perpetuating the privilege and status of elite and powerful groups.